Implementasi Regulasi Penerimaan Negara Bukan Pajak Sektor Batubara Berdasarkan Hukum Keuangan Negara di Kabupaten Muara Enim - Rachmadita Sheila Alikaputri; Waluyo; Rahayu Subekti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study examines the implementation of Non-Tax State Revenue regulations in the coal sector in Muara Enim Regency from the perspective of state financial law. The coal sector contributes significantly to state revenue with realization reaching Rp 140.46 trillion in 2024. Normative legal research methods were employed using statutory and conceptual approaches to analyze regulatory implementation based on Law Number 17 of 2003 concerning State Finance and Government Regulation Number 26 of 2022. Research findings indicate that the collection mechanism has been structured through a self-assessment system supported by the e-PNBP application with clear division of authority between central and regional governments. However, implementation still faces obstacles including limited apparatus understanding of regulatory complexity, minimal information technology infrastructure, weak inter-agency coordination, and low transparency and accountability in management. Supporting factors include substantial coal reserves, local government commitment, and digital reporting systems. Harmonization of authority between central and regional governments requires strengthening through regulatory synchronization, institutional capacity enhancement, and improvement of integrated supervision systems to optimize state revenue while supporting regional development within the framework of regional autonomy and fiscal decentralization.